Long‐term risk of seizure after posterior reversible encephalopathy syndrome. Issue 4 (22nd February 2023) - Seitz, Alison; Parauda, Sarah C.; Salehi Omran, Setareh; Schweitzer, Andrew D.; Liberman, Ava L.; Murthy, Santosh B.; Merkler, Alexander E.; Navi, Babak B.; Iadecola, Costantino; Kamel, Hooman; Zhang, Cenai; Parikh, Neal S.
Abstract: Objective: Patients with posterior reversible encephalopathy syndrome (PRES) can develop seizures during the acute phase. We sought to determine the long‐term risk of seizure after PRES. Methods: We performed a retrospective cohort study using statewide all‐payer claims data from 2016–2018 from nonfederal hospitals in 11 US states. Adults admitted with PRES were compared to adults admitted with stroke, an acute cerebrovascular disorder associated with long‐term risk of seizure. The primary outcome was seizure diagnosed during an emergency room visit or hospital admission after the index hospitalization. The secondary outcome was status epilepticus. Diagnoses were determined using previously validated ICD‐10‐CM codes. Patients with seizure diagnoses before or during the index admission were excluded. We used Cox regression to evaluate the association of PRES with seizure, adjusting for demographics and potential confounders. Results: We identified 2095 patients hospitalized with PRES and 341, 809 with stroke. Median follow‐up was 0.9 years (IQR, 0.3–1.7) in the PRES group and 1.0 years (IQR, 0.4–1.8) in the stroke group. Crude seizure incidence per 100 person‐years was 9.5 after PRES and 2.5 after stroke. After adjustment for demographics and comorbidities, patients with PRES had a higher risk of seizure than patients with stroke (HR, 2.9; 95% CI, 2.6–3.4). Results were unchanged in a sensitivity analysis that applied a two‐week washout period to mitigate detection bias. A similar relationship was observed for the secondary outcome of status epilepticus. Interpretation: PRES was associated with an increased long‐term risk of subsequent acute care utilization for seizure compared to stroke.